The reasons of the «Arab Spring» in the coverage of Russian and Local scientists-orientalists - Aмирбековa С. К.; Бaйдaров Е. Ұ. (Journal of Oriental Studies, 2017)
This article is devoted to the complex analysis of the views of Russian and Local scientists and orientalists about the social and political upheaval in the Arab Middle East, which have been affected by the events of the «Arab Spring». Scientists and orientalists have attempted to analyze the events that took place from 2011 to 2013 in the Arab East, as well as a detailed study of the causes of popular unrest, and given the characteristics of the basic processes that have evolved in the Middle East.